ANTI-QUORUM SENSING ACTIVITY OF 1, 3-DIHYDRO-2H-BENZIMIDAZOL-2-ONE DERIVATIVES - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2018)
Many Gram-negative bacteria use N-acyl homoserine lactone (AHL) signal molecules to monitor their own population density and coordinate gene regulation in a process called quorum sensing (QS). Pseudomonas aeruginosa controls production of virulence factors (elastase, pyocyanin or swarming motility) via QS. The discovery that QS system regulates bacterial virulence has afforded a novel opportunity to control infections without interfering with growth. The aim of this study was to investigate antiquorum sensing effect of synthesized benzimidazole derivatives which are N-acyl homoserine lactone analogs. All chemicals synthesized as quorum sensing inhibitors were tested against virulence factors-elastase, pyocyanin, swarming motility-in Pseudomonas aeruginosa PA01. Firstly 1,3-dihydro-2H-benzimidazol-2-one (U65), 5-methyl-1,3-dihydro-2H-benzimidazol-2-one (U77) and 1,3-diacetyl-1,3-dihydro-2H-benzimidazol-2-one (U92) were screened for anti-quorum sensing activity using a biomonitor strain, Quorum Sensing Selector Strain 1 and Chromobacterium violaceum CV026, Chromobacterium violaceum VIR07. All of the synthesized compounds showed anti-QS activity and exhibited significant inhibitory effect on production of elastase, pyocyanin and swarming motility. In conclusion, our results demonstrated that synthesized benzimidazole derivatives inhibited bacterial communication in Pseudomonas aeruginosa which is crucial for the infections and further studies of these molecules should be investigated on other bacteria.
Keywords: Quorum-sensing inhibitors; virulence; benzimidazole; P.ae- ruginosa PA01; PSEUDOMONAS-AERUGINOSA; ANTIMICROBIAL RESISTANCE; INHIBITORS; SURVEILLANCE; EXPRESSION; PATTERNS